Fire forecasts 2021: Southern Amazon - Castaño, Silvia-Elena; Fernandes, Kátia; Morton, Douglas; Carvajal, Andrea; Staiger Rivas, Simone (2021)
2021 forecasts show average fire risk in the southern Amazon, in contrast to 2020. Fires in the Amazon are the result of human activities, including the use of fire for deforestation, land clearing and agricultural maintenance. Most fires begin in non-forest areas that have already been cleared for agricultural use, but these fires can escape into neighboring forests and burn through the understory. Even these low-intensity surface fires kill most trees, since Amazon forests are not adapted to fire. Main results disseminated through the ArcGIS Storymap App: https://storymaps.arcgis.com/stories/a6f868ce2703464cbf6da2073c9ec5f0 (English) https://storymaps.arcgis.com/stories/5008dafea8f743e6b9e95d43ed5f9370 (Español) https://storymaps.arcgis.com/stories/7562d00c2d3c4457af7941812eb4b20a (Português)